Case report of a juvenile patient with autism spectrum disorder with a novel vombination of vopy number variants in ADGRL3 (LPHN3) and two pseudogenes - Maurer, Martin H.; Kohler, Anja; Hudemann, Melanie; Jüngling, Jerome; Biskup, Saskia; Menzel, Martin (The application of clinical genetics, 2022)
To our knowledge, this is the first report of a copy number variant in the ADGRL3 gene, and its first association with autism spectrum disorder in humans.
Gesehen am 23.04.2024